2017
DOI: 10.1083/jcb.201607048
|View full text |Cite
|
Sign up to set email alerts
|

Microglia control the glycinergic but not the GABAergic synapses via prostaglandin E2 in the spinal cord

Abstract: Microglia can influence the excitatory responses of neurons, but less is known about how these immune cells in the brain may influence inhibitory neurotransmitters. Cantaut-Belarif et al. report that prostaglandin production by Toll-like receptor–stimulated microglia can influence the glycinergic but not GABAergic responses of neurons by altering the lateral diffusion of glycine receptors specifically within the synaptic membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 65 publications
2
39
0
1
Order By: Relevance
“…The higher PPR, together with the higher failure rate observed under conditions of minimal stimulation, strongly argues for a reduction in the probability of transmitter release in KO mice (Stevens & Wang, ). Moreover, our results in the minimal stimulation paradigm, showing that the potency is normal in KO synapses, and the previously reported similar mEPSC amplitudes in WT and KO (Zhan et al, ) argue against a postsynaptic mechanism, like those reported previously (Cantaut‐Belarif et al, ; Ragozzino et al, ). In addition, we found no differences in the increase in potency, typically seen at high release probability, suggesting that the number of release sites or vesicles is unchanged in the KO (Isaac et al, ; Stevens & Wang, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The higher PPR, together with the higher failure rate observed under conditions of minimal stimulation, strongly argues for a reduction in the probability of transmitter release in KO mice (Stevens & Wang, ). Moreover, our results in the minimal stimulation paradigm, showing that the potency is normal in KO synapses, and the previously reported similar mEPSC amplitudes in WT and KO (Zhan et al, ) argue against a postsynaptic mechanism, like those reported previously (Cantaut‐Belarif et al, ; Ragozzino et al, ). In addition, we found no differences in the increase in potency, typically seen at high release probability, suggesting that the number of release sites or vesicles is unchanged in the KO (Isaac et al, ; Stevens & Wang, ).…”
Section: Discussionsupporting
confidence: 89%
“…Although we cannot entirely rule out more complicated mechanisms, including the above mentioned presence of subpopulations of synapses contributing preferentially to the KO deficit under different conditions of stimulation, we favor the interpretation that the KO phenotype is primarily the result of a presynaptic maturation deficit. In contrast, an intriguing way to explain our results, would be that synapses continuously need microglia interaction (by contact or soluble factors) for their correct functioning (Cantaut‐Belarif et al, ; Parkhurst et al, ). Further studies will be necessary to understand the cellular and molecular mechanisms underlying the specific effect of microglia on presynaptic function and to determine whether similar processes are important in the development of other brain structures and in synaptic plasticity during normal and pathological states in adulthood (Parkhurst et al, ; Schafer et al, ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This demonstration adds one more line of evidence to the emerging theme of microglia as a modulator of neurotransmission (Cantaut-Belarif et al, 2017;Marrone et al, 2017). Intranasal administration of an NGF variant was recently proven to be highly neuroprotective in an AD mouse model: 53FAD mice chronically treated with the neurotrophin showed a dramatic reduction of the plaque load, with a clear evidence of the involvement of microglial cells in the clearance of Ab (Capsoni et al, 2017).…”
Section: Discussionmentioning
confidence: 71%
“…In addition to the complement‐mediated mechanism, astrocyte‐derived interleukin (IL)‐33 is also physiologically required to maintain synapse homeostasis by modulating microglial synapse engulfment (Vainchtein et al, ). Microglia are involved in regulating and shaping both excitatory and inhibitory synapses, such as γ‐aminobutyric acid‐expressing and glycinergic synapses (Cantaut‐Belarif et al, ; Um, ). Conversely, early evidence obtained from CX3CR1 gene‐deleted mice indicated that reduced numbers of microglial cells during brain development could impair the processes of synaptic pruning, resulting in a significantly higher density of dendritic spines and immature synapses (Paolicelli et al, ; Shibata & Suzuki, ).…”
Section: Multi‐tasking Microglia: a Friend For Brain Homeostasismentioning
confidence: 99%